1996
DOI: 10.1097/00000539-199601000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Response to Intravenous Lidocaine in the Treatment of Neuropathic Pain

Abstract: This study was performed in order to determine concentration-effect, and graded and quantal dose-response relationships for the clinical administration of intravenous (IV) lidocaine to patients with neuropathic pain. Thirteen patients were administered 500 mg of IV lidocaine at a rate of 8.35 mg/min over 60 min. Visual analog pain scores and venous blood samples were obtained concomitantly at 10 min intervals for 60 min. Blood samples were also obtained for determination of serum and serum water lidocaine conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
61
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 14 publications
3
61
1
Order By: Relevance
“…The analgesic effects of lidocaine observed in our patients did not different among 1 mg/kg and 5 mg/kg of lidocaine.Results of the present study which VAS was decreased correspond with the results of earlier studies [6,7,16,17]. This suggests that lidocaine produces a dose-related reduction of afferent activity from dorsal root ganglion [8-10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The analgesic effects of lidocaine observed in our patients did not different among 1 mg/kg and 5 mg/kg of lidocaine.Results of the present study which VAS was decreased correspond with the results of earlier studies [6,7,16,17]. This suggests that lidocaine produces a dose-related reduction of afferent activity from dorsal root ganglion [8-10].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the free concentration of lidocaine showed no better correlation with the onset of analgesia or the attainment of complete analgesia than the serum concentration of lidocaine. Ferrante et al [17] suggested that the mechanism of analgesia from IV lidocaine is not being based upon a conventional concentration-effect relationship and there was not a direct relationship between total or free lidocaine levels and the effect on neuropathic pain [15]. However, we did not determine the blood levels of lidocaine.…”
Section: Discussionmentioning
confidence: 87%
“…Clinical use of non-selective Na + channel blockers lidocaine and its analogue mexiletine appear to be effective on some neuropathic pain symptoms, the efficacy being non-dose dependent and the centrally-mediated side-effects are not well tolerated (Attal et al, 2004; Ferrante et al, 1996; Finnerup et al, 2005; Wallace et al, 2000). In a previous study, the highest tested dose of mexiletine (75 mg/kg) did not ameliorate either mechanical or heat hypersensitivity in SCI rats (Hama and Sagen, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ambroxol’s effect on mechanical hypersensitivity was restricted to the highest tested dose, similar to that observed in peripheral nerve-injured rats (Gaida et al, 2005). The all-or-none effect with Na + channel blocking drugs has also been clinically observed (Ferrante et al, 1996). The high dose-only effect could be related to the limited distribution of Na v 1.8 in large-diameter mechano-sensitive primary afferents in contrast to the abundant expression of Na v 1.8 in small-diameter nociceptors.…”
Section: Discussionmentioning
confidence: 99%
“…15 In the second study, pain in 5 patients with various neuropathic syndromes was reduced when toxic lidocaine levels (Ͼ3 g/mL) were achieved following a total dose of 3 mg/kg. 16 Non-sodium channel mechanisms are also plausible explanations for the antihyperalgesic actions of lidocaine, including inhibition of substance P, 17 NMDA receptors, 18 and glutamate activity. 19 A study using the isolated arm technique in humans 20 supports a peripheral analgesic effect of regional intravenous infusion of lidocaine on the development of mechanical-induced hyperalgesia and histamine-induced itching, but not touch perception and heat-induced nociception.…”
Section: Discussionmentioning
confidence: 99%